Sensor-free corner shape detection by wireless networks - WANG, Yuxi (Institutional Knowledge at Singapore Management University, 2014)
Due to the rapid growth of the smartphone applications and the fast development of the Wireless Local Area Networks (WLANs), numerous indoor location-based techniques have been proposed during the past several decades. Floorplan, which defines the structure and functionality of a specific indoor environment, becomes a hot topic nowadays. Conventional floorplan techniques leverage smartphone sensors combined with WiFi signals to construct the floorplan of a building. However, existing approaches with sensors cannot detect the shape of a corner, and the sensors cost huge amount of energy during the whole floorplan constructing process. In this paper, we propose a sensor-free approach to detect the shape of a certain corner leveraging WiFi signals without using sensors on smartphones. Instead of utilizing traditional wireless communication indicator Received Signal Strength (RSS), we leverage a finer-grained indicator Channel State Information (CSI) to detect the shape of a certain corner. The evaluation of our approach shows that CSI is more robust in sensor-free corner shape detection, and we have achieved over 85% detection accuracy in simulation and over 70% detection accuracy in real indoor experiments.